Defiance to the social normalities: Misrepresentation of mad women in American literary Landscapes: Article on Madness - Muhammad Ijaz; Syed Ali Raza; Amir Asim, Muhammad Amir (JSSH, 2024)
Abstract This study expatiates upon the factors that lead the women towards their madness and provide the justifications for labeling them as mad women. It examines the ways that are adopted by dominant forces of the society to formulate systems of superiority and to maintain them. The study is set to unpack the patriarchal mechanisms that suppress all opposing voices against them. Moreover, it foregrounds feministic approaches that seek to contradict the established societal norms. Importantly, the study scrutinizes the changing feministic attitudes in the European and American landscapes during the nineteenth and twentieth century. To strengthen its findings, the study is premised on fiction produced by female writers from Euro-American backdrops. It includes Kate Chopin’s The Awakening (1899) and Silvia Plath’s The Bell Jar (1963). The study comprises a comparison of the selected texts to explore the reasons of women’s madness and representation of such women in literary landscapes. As the study explores the nature of existing relationship between both genders, it applies certain conceptions of feminist criticism to scrutinize power relationship between the genders. The study finds that female tendency to challenge established patriarchal norms provides the dominant forces a justification to pronounce defiant women as mad. Women’s expectation of equal social, moral and economic patterns is conceived of as a threat to prevailing dominant power structures. Such dominant elements declare challenging female voices as abnormal and mad and suggext special treatment for them. Key words: Madness, Patriarchy, Femininity, Individuality, Supression